Integritas Pajak Digital: Peran Moderator E-Filing dan Coretax Terhadap Determinan Kepatuhan Wajib Pajak - Sonny Sonny; Estralita Trisnawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study investigated the influence of Tax Knowledge, Awarenes and Ethics on taxpayer compliance specifically examining the moderating role of E-Filing and the Core Tax System.The research, conducted at KPP Pratama Batam Selatan, utilized a quantitative approach with a sample of 100 taxpayers. Primary data were collected via questionnaires and analyzed using PLS-SEM method with SmartPLS 3.0. The empirical findings that Taxpayer Compliance is positively significantly influenced by Tax Knowledge, Awareness and Ethics across all tested models. E-Filing successfully strengthens the positive influence of both Tax Knowledge and Awareness on compliance, proving to be an effective technological enabler. Conversely, the Core Tax System was found to be effective only in moderating Tax Awareness, showing no significant effect on Tax Knowledge or Tax Ethics, likely due to technical implementation constraints. This affirms that enhancing compliance requires not only strong internal factors but also reliable, user-friendly administrative systems supported by ongoing education and moral development